Challenges and possibilities of WSNs in the dynamic monitoring of existent structures - Aguilar, Rafael (2011)
In the field of monitoring sensors, the progress of new technologies, such as wireless communications and Micro-Electro-Mechanical-Systems – MEMS are of high interest as alternatives for the expensive and handle difficult wired-based sensors. The incorporation of these new technologies in the structural health monitoring and preservation of cultural heritage buildings would definitely represent a turning point of the testing techniques and experimental methodologies. This paper presents a detailed analysis of the Wireless Sensor Networks (WSNs) technology when used for carrying out dynamic monitoring studies in existent structures. For this purpose, commercial off-the-shelf (COTS) solutions as well as a new platform, especially developed in the University of Minho for performing operational modal analysis tests, were used in laboratory and real field tests. The results show that COTS systems are not accurate and reliable enough for these kinds of tests due to the low resolution of sensors, and ADCs embedded as well as the lack of implementation of communication protocols. On the other hand, the results of the new system evidenced high accurate time domain acquisitions which indicate precise estimations of the structural dynamic properties.